Public-Private Collaboration: public capacities to manage the model developed by the State Public Employment Services and Private Employment Agencies - García Solana, María José (Cuadernos de Gobierno y Administración Pública, 2017)
This article addresses, in the context of governance, the competencies and capacities that public actors must assume in order to achieve success in the implementation of collaborative strategies, such as public-private collaboration. The need for a strong, leader and effective management is a key in collaborative process, but for this it is necessary to detect the capabilities that guarantee the develop of the model. This analysis is based on the study of the public-private partnership developed by the SEPE and the private agency in the intermediation service of employment policy. The analysis shows the importance of strengthening public capacities like an objective to guarantee the stability and transparency model and ensure the participation of stakeholders.
Keywords: governance; public-private collaboration; employment policy; employment public service; private employment agencies.